(untitled) (Journal of International Studies, 2013)
В статье показано развитие русско-монгольских отношений в первой четверти XX века, становление монгольского национального государства и роль России; представлена современная характеристика исследований данной проблемы в российской и монгольской историографии. Questions of Russian-Mongolian Relations in the Beginning of 20th century (1900-1921): Economics, Diplomacy and Culture The development of Russian-Mongolian relations in the first quarter of XX century, formation of the Mongolian national state ant the role of Russia in this process are mentioned in this article; the modern characteristic of researches of these problems in Russian and Mongolian historiography is also presented.